Media sosial dan Perilaku Keberagamaan Santri Remaja di Pondok Pesantren Nurul Huda Kajen - Laily, Nurul (FIKRAH, 2018)
This article discusses the relationship between social media and the religious behavior of students in the Nurul Huda Kajen Islamic Boarding School. Santri in the pesantren can access social media as a place to get to know the world, but the problem is how the students use and use social media whether it is appropriate or not. This article aims to describe the usefulness and behavior of students in the Nurul Huda Kajen Islamic Boarding School in Margoyoso district, Pati regency. This article includes the field research article type with qualitative approach techniques. Data collection techniques include interviews, observation and documentation. The results of the article show two behavioral models of santri after getting to know positive and negative social media. The positive is to dig up information that helps learning and negativity is the loss of santri responsibility for the behavior that has been done. The solution is for santri to be equipped with a comprehensive understanding of religion in order to maintain religious values when using social media, and away from criminal behavior.